7.3 PECULIARITIES OF THE EXPLOITATION OF TRACKLESS TRACK AND THE DAMAGE OF RAILROAD TRACK SHOULDERS BY DEFECTS - Begmatov Pardaboy Abdurakhimovich, Associate Professor Eshonov Farhod Faizullaevich, Senior Lecturer (Innovative technologies in construction Scientific Journal, 2024)
The paper considers rail defects in high-speed sections of railroad track and analyzes temperatures under different modes. Key words: rail, trackless track, rail defects, rail stresses. Increase in the intensity of track operation is accompanied by an increase in the force impact of wheels on rails. This is due to the increase of static load and growth of dynamic additives caused by the increase of track stiffness due to the laying of reinforced concrete sleepers and rails of heavy types. The effect of additional impact of rolling stock on the track is mainly in the rail head. This is where most of the rail damage occurs and develops: the share of single railroads withdrawn from the track due to defects in the rail head on the road network. Consequently, for a considerable period of time rails are operated on the track with localized damage in the form of cracks, with the development of which to a certain critical size sharply increases the probability of brittle fracture of rails under the train along the defective section. This is clearly evident from VNIIJT materials: about 1/3 of all train accidents occur due to rail fracture, out of the annual total number of rail failures on the road network. The study of the peculiarities of damageability of rails, including ties, by defects in [1] is summarized in Tables 1. To improve the system of rail maintenance, it is necessary to develop measures to reduce train delays during the operation of defective ties of trackless track, since on the sections with medium and high load tension a significant part of rail failures occurs due to defects. Distribution of defective and acutely defective rails removed from the track by type Table 1. Type of defect % of total Type of defect % of total 11 4,2/2,4 26,3 1,1/4,9 14 4,7/1,8 30 4,8/1,5 17 4,3/0,6 41 3,5/0,3 21 46/84,7 44 13,5/0,8 24 0,5/- 53,1 17,4/3,0 Elimination of such defects in the braids causes difficulties in ensuring the throughput capacity of the section due to the need to provide two two-hour "windows" and limit the speed of trains when cutting out defective places both during temporary restoration of the continuity of the braids and during the final restoration of the integrity of the braids by welding a piece of rail of the required length instead of a temporary rail using a special technology, with preliminary trimming of the ends of the braids with bolt holes. The development of progressive technology for the restoration of defective rail splices was based on the results of research performed at VNIIJT by V.L. Poroshin and E.M. Blomberg [2,3,5]. Е. A. Shur [5]. Defectoscopic diagnostics of rails in the track can detect transverse cracks in the rail head, classified as a defect, the area F 5-105 of the head cross-section Fg , and all rails with defects are considered acutely defective rails and are subject to immediate removal from the track.